Penerapan model pembelajaran kooperatif Numbered Head Together (NHT) untuk meningkatkan keaktifan dan hasil belajar matematika materi satuan kecepatan - Rahmawati, Annissya Nuraini; Siti Poerwanti, Jenny Indrastoeti; Sularmi, Sularmi (Universitas Sebelas Maret, 2022)
The purpose of this study was to increase student activity and learning outcomes through the application of the Numbered Head Together (NHT) cooperative learning model on the speed unit material for fifth grade students at SD Negeri Karangasem IV Surakarta in the 2021/2022 academic year. This research is a classroom action research which is carried out in two cycles. Each cycle consists of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. Data collection techniques through observation, interviews, test, and documentation. The results showed: 1) The percentage of learning activity completeness in cycle I was 53.13%, increased to 81.25% (26 of 32 students) active with a high category in cycle II; 2) The percentage of complete learning outcomes of students after the implementation of the NHT learning model in the first cycle is 71.88% with an average grade of 75.35. In the second cycle, it increased to 81.25% with an average class value of 80.63. Based on the results of the study, it was concluded that the application of the NHT cooperative learning model could increase the activeness and learning outcomes of students in class V on the speed unit material at SDN Karangasem IV Surakarta.